2015
DOI: 10.1155/2015/396107
|View full text |Cite
|
Sign up to set email alerts
|

Mucolytics for Intubated Asthmatic Children: A National Survey of United Kingdom Paediatric Intensive Care Consultants

Abstract: Aim. The extent to which mucolytics are utilised in mechanically ventilated asthmatic children is unknown. We sought to establish current practice in the United Kingdom (UK) including choice of mucolytic, dose, and frequency of utilisation. Methods. A national electronic survey was distributed to UK consultants during April and May 2014. We were able to identify 168 PICU consultants at 25 institutions to whom we were able to electronically distribute a survey, representing an estimated 81% of UK NHS PICU consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(29 reference statements)
1
5
1
Order By: Relevance
“…DNase was delivered via nebulisation and instillation, whereas hypertonic saline was predominantly nebulised. This is in line with practice described in published literature (den Hollander et al, 2020, Snoek andBrierley, 2015).…”
Section: More Extensive Research Has Been Completed In Adult Icus And...supporting
confidence: 92%
See 1 more Smart Citation
“…DNase was delivered via nebulisation and instillation, whereas hypertonic saline was predominantly nebulised. This is in line with practice described in published literature (den Hollander et al, 2020, Snoek andBrierley, 2015).…”
Section: More Extensive Research Has Been Completed In Adult Icus And...supporting
confidence: 92%
“…All physiotherapists in this study reported using at least one mucoactive agent, with hypertonic saline and DNase the most popular. In a UK survey of mucoactive use for ventilated asthmatic children, 63% (55/87) of PICU consultants reported using DNase and 54% (46/85) hypertonic saline (Snoek and Brierley, 2015).…”
Section: More Extensive Research Has Been Completed In Adult Icus And...mentioning
confidence: 99%
“…17 Although our data do not support routine use of hypertonic saline in mechanically ventilated children, survey data show that hypertonic saline is prescribed routinely during mechanical ventilation by a large number of pediatric ICU physicians. 18 Our study provides these practitioners with previously unavailable data pertaining to adverse effects of hypertonic saline in children undergoing mechanical ventilation. We are unaware of any prior prospective data reporting the incidence of post-hypertonic saline wheezing in ventilated children.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence of a clinical benefit of dornase alfa in children [90] or adults [91] with moderate to severe asthma. Nevertheless, some clinicians appear to use dornase alfa in mechanically ventilated children, [92] fueled by case reports showing improvement agent [93,94]. The administration of NAC in asthma has met with very limited success, as more recently assessed in a systematic review and meta-analysis.…”
Section: Asthmamentioning
confidence: 99%